Music as a Tool in Learning: Improvements in Basic Competences in Children Studying an Integrated Music Programme - Llorenç Gelabert Gual; Noemy Berbel Gómez; Víctor Alejandro Sanchez-Azanza (Revista Electrónica Complutense de Investigación en Educación Musical, 2023)
Son Serra (Son Serra State Primary School), in Mallorca, is the first state-run school in the Balearic Islands to offer integrated music and non-integrated pathways to students in the same class. This study aims to compare the results of students from the fourth year of primary education from both pathways in a maths, Spanish, Catalan and English language level tests. Socioeconomic information on the children's families was also gathered. The results showed students from the integrated music group always outperforming their peers from the non-integrated group in the four assessed competences. Having established that the families’ socioeconomic status does not condition these results, the benefits of receiving more music practice were discussed.